Earliest expansion of animal husbandry beyond the Mediterranean zone in the sixth millennium BC - Ethier, Jonathan; Ivanova-Bieg, Maria (Scientific reports, 2017)
Since their domestication in the Mediterranean zone of Southwest Asia in the eighth millennium BC, sheep, goats, pigs and cattle have been remarkably successful in colonizing a broad variety of environments. The initial steps in this process can be traced back to the dispersal of farming groups into the interior of the Balkans in the early sixth millennium BC, who were the first to introduce Mediterranean livestock beyond its natural climatic range. Here, we combine analysis of biomolecular and isotopic compositions of lipids preserved in prehistoric pottery with faunal analyses of taxonomic composition from the earliest farming sites in southeast Europe to reconstruct this pivotal event in the early history of animal husbandry. We observe a marked divergence between the (sub)Mediterranean and temperate regions of Southeast Europe, and in particular a significant increase of dairying in the biochemical record coupled with a shift to cattle and wild fauna at most sites north of the Balkan mountain range. The findings strongly suggest that dairying was crucial for the expansion of the earliest farming system beyond its native bioclimatic zone.